Electrochemical behaviour of martensitic stainless steel after immersion in a H2S-saturated solution. (February 2018) - Lei, Xiaowei; Wang, Hongyan; Mao, Feixiong; Zhang, Junping; Zhao, Mifeng; Fu, Anqing; Feng, Yaorong; Macdonald, Digby D.
Highlights: The electrochemical behaviour of Super 13Cr martensitic stainless steel was analysed after immersion in a H2 S-saturated solution. The corrosion resistance of Super 13Cr decreased dramatically with increasing the exposure time, and the barrier layer is highly defective. Depassivation occurred after long-term exposure to the H2 S-containing media. Abstract: Time dependent experiments were carried out to study the corrosion behaviour of Super 13Cr martensitic stainless steel after immersion in a H2 S-saturated solution. The Point Defect Model was employed to obtain key parameters. With increasing immersion time, the corrosion product layer thickened, but displayed a defective structure. The thickness of the barrier layer decreased with extending the H2 S-exposure time, which notably lowered the corrosion resistance. The presence of the corrosion scale resulted in a thinner barrier layer in contrast to that without the scale. With/without the corrosion scale, no semi-conductivity and no passive region was observed for Super 13Cr after 96 h-immersion. The hydrogen ingress during H2 S-exposure lowered the passivity of the bare alloy substrate.